PERAN PENDIDIKAN KEWARGANEGARAAN TERHADAP MORAL SISWA - Nicki Wijaya Kusuma (ADIBA : JOURNAL OF EDUCATION, 2025)
The role of citizenship education is to develop citizens, especially the nation's next generation, which is beneficial for the life of the nation and state. Citizenship education for the nation's next generation is very important to raise awareness of defending the country and increase the feeling of love for the country. Using Qualitative Research Types and Approaches. Data collection techniques use interviews and observation. This technique is used to obtain significant and appropriate data. Thus, the results of this research can be concluded that the role of Citizenship Education on student morals. The results of this research aim to increase insight into how to apply Citizenship Education learning procedures in improving student morale, as well as broadening teacher insight in educating and creating good student character and morals.